2007
DOI: 10.1094/pdis-91-12-1621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oriental Medicinal Plant Extracts on Spore Germination ofAlternaria brassicicolaand Nature of Inhibitory Substances from Speedweed

Abstract: Among 65 species of oriental medicinal plants tested, 39 contained substances inhibitory to conidial germination of Alternaria brassicicola, with the most inhibitory extract from speedweed (Polygonum perfoliatum). The inhibitory substances in dried speedweed were insoluble in water. However, the inhibitors were readily extracted with ethanol or methanol, but not with acetone, ether, or chloroform. The ethanol extract was very effective in controlling black leaf spot of spoon cabbage, Brassica campestris subsp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This current experiment provided some scientific justification for the utilization of extracts from these plants to treat fungal diseases. Of the 65 species of oriental medicinal plants tested by Ho et al (2007),60% contained substances inhibitory t o spore germination of Alternaria brassicicola and they suggested that oriental medicinal plants are a good source for obtaining desirable substances for controlling pathogenic fungi. No toxicity or antitumor activity were recorded for the tested plant extracts up to 600 pg/ml except for A.…”
Section: Resultsmentioning
confidence: 99%
“…This current experiment provided some scientific justification for the utilization of extracts from these plants to treat fungal diseases. Of the 65 species of oriental medicinal plants tested by Ho et al (2007),60% contained substances inhibitory t o spore germination of Alternaria brassicicola and they suggested that oriental medicinal plants are a good source for obtaining desirable substances for controlling pathogenic fungi. No toxicity or antitumor activity were recorded for the tested plant extracts up to 600 pg/ml except for A.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of mixture was adjusted to 5.7 and filtered through Whatman no. 1 filter paper after shaking for 30 min (Ho et al 2007). To study the effect of antioxidant on the incidence of lethal browning of banana tissue culture plantlets, 10 ml of 0.01% ascorbic acid solution was added to the surface of SM medium in each flask after autoclaving.…”
Section: Addition Of Adsorptive or Antioxidant Materials To Mediummentioning
confidence: 99%
“…To test the nature of the inhibitor in the culture filtrate of C. nuda (LA82), 10 g each of Diaion SK1B cation exchange resins (equivalent to Amberlite IR-120), Diaion SA12A anion exchange resins (equivalent to Amberlite IRA-420) (Tai-Young Chemical Co., Kaohsiung, Taiwan), or activated charcoal (Sigma-Aldrich, USA) were washed with 100 ml of distilled water four times by shaking for a 6-h period to remove possible inhibitory substances [25]. Fifty milliliters of culture filtrate was shaken with either 5 g of each type of resins or 5 g of activated charcoal in a 250-ml flask at 150 rpm for 24 h and filtered through a Whatman No.…”
Section: Effect Of Adsorptive Materials On the Inhibitory Activitymentioning
confidence: 99%
“…Fifty milliliters of culture filtrate was shaken with either 5 g of each type of resins or 5 g of activated charcoal in a 250-ml flask at 150 rpm for 24 h and filtered through a Whatman No. 1 filter paper [25]. The treated culture filtrates were used for germination tests.…”
Section: Effect Of Adsorptive Materials On the Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation